Hydrogen as Future Fuel Used in Minimum Change Derivatives of the Airbus A321 - Dieter Scholz and Leon Dib (Deutsche Gesellschaft für Luft- und Raumfahrt – Lilienthal-Oberth e. V., 2015)
A new concept of a passenger aircraft using hydrogen as fuel is presented. Due to the future depletion of fossil fuels and growth of aviation within the next years, the aeronautical industry must get ready now for a realistic solution. Many projects were conducted for hydrogen-fueled aircraft designs in the past, however all the effort was focused on an expensive totally new aircraft design. In this work, research is based on the Airbus A320 with a requirement for 1510 NM range at 19.3 t maximum payload. Goal is to redesign the aircraft under the premise of minimum change and minimum costs. Hydrogen as the new energy carrier will be stored at cryogenically temperatures. Still it needs more tank volume. This extra volume is best generated with an aircraft stretch leading to an increase of aircraft length. A minimum change option would be to simply use A320 seating in an A321, using the additional space for the new hydrogen fuel tanks. Unfortunately, the additional volume on its own is not sufficient. Therefore, three different hydrogen-fueled versions are developed. 1.) The A321-HSO stretched beyond the length of the A321. 2.) The A321-HWO with A321 fuselage and additional under-wing podded hydrogen fuel tanks. 3.) A321-H19O with A321 fuselage and A319 cabin. All three versions were designed and optimized in OPerA, the in-house conceptual design and optimization program based on a genetic algorithm. Objective function for the optimization are minimum Direct Operating Costs (DOC). Assumed is a price for hydrogen, energy-equivalent to kerosene and estimated for 2030 to be 1.12 USD/kg. All three versions stayed in feasible dimensions. The weight of the aircraft is decreased between 3.4% (A321-H19O) and 0.7% (A321-HSO). Depending on the version considered, the DOC of the aircraft is increased by 20% to 30%. Hydrogen aircraft do not show CO2 emissions, releasing only water vapor, NOx and particles into the air. However, water emitted at altitude can form cirrus clouds. This effect on global warming is presently not fully understood. The result: If fossil fuels get near to depletion and kerosene gets so scarce that the price of hydrogen matches that of kerosene, passenger air transport remains available with hydrogen-fueled minimum change conversions of existing aircraft types.
Keywords: Luftfahrt; Luftfahrzeug; Flugzeugentwurf; Wasserstoff; aviation; aircraft; design; hydrogen; fuel; passenger